(untitled) (Homiletic, 2015)
The Australian National Church Life Survey identifies churches where the preaching is reported as “very helpful to my life.” Six case studies of these churches were undertaken. Observation, interviews, focus groups, and a survey were used in each case to identify salient descriptors. A number of features common to all cases are discernible including, practicality, humor, passion, boldness, intellectual stimulation and a simple structure. However, the research also confirms that preaching is a highly contextual activity and that preachers need to adapt their style to their particular context. A continuum of helpful preaching styles related to context is developed.